1981
DOI: 10.1111/j.1751-0813.1981.tb05837.x
|View full text |Cite
|
Sign up to set email alerts
|

Helminth Parasites and Arthropods of Feral Cats

Abstract: The prevalence (%) of helminth parasites in 327 mainly adult feral cats from 3 habitat groupings in Victoria and New South Wales was determined. The cestodes Taenia taeniaeformis (33%) and Spirometra erinacei (33%) were common; Dipylidium caninum was rate (2%). The nematodes Toxocara cati (28%), Cyathospirura dasyuridis and Cylicospirura felineus combined (27%) and Aelurostrongylus abstrusus (14%) were common but their prevalence differed markedly between habitats. Ollulanus tricuspis (5%), Gnathostoma spinige… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
29
2
4

Year Published

1985
1985
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(39 citation statements)
references
References 15 publications
4
29
2
4
Order By: Relevance
“…16 Toxocara cati, the cat round worm, has been reported as occurring in feral cats throughout Australia, at varying prevalence. [8][9][10][11][12][13][14][15] The role of intermediate hosts,…”
Section: Discussionmentioning
confidence: 99%
“…16 Toxocara cati, the cat round worm, has been reported as occurring in feral cats throughout Australia, at varying prevalence. [8][9][10][11][12][13][14][15] The role of intermediate hosts,…”
Section: Discussionmentioning
confidence: 99%
“…However, the other species have not been previously reported. It was reported that C. canis was the dominant species in Dublin [14], rural England [13], and Australia [15]. However, Harman et al [26] reported that C. canis was not identified among the dogs examined for fleas in Florida.…”
Section: C B Amentioning
confidence: 99%
“…Birçok ülkede kedi parazitleri ilc ilgili pekçok araştırma yapılmış, araştırma sonuçları ülkeden ülkeye, şehirden şehire hatta aynışehirde yapılandeğişik çalışmalarda yıldan yıla farklılıklar göstermiştir (3,7,12,19,20,21,23 Bu araştırmada kontrol edilen 100 sokak kedisinin 96 sında (% 96) 16 parazit türü bulunmuş olup artropod parazitlere en az, helmintlere ise gerek artropod gerekse protozoonlara oranla daha çok rastlanmıştır. Parazitlerle enfeksiyon oranının çok yüksek olduğu dikkati çekmiştir.…”
Section: Tartışma Ve Sonuçunclassified
“…da halk ve çevre sağlığı açısından önem taşımaktadır. Bazı paraziderin yayılmasında veya insanlara ta~ınmasında kedilerin oynadığı role dikkat çekilmi~(1,2, i i, 18,22,25) Dış ülkelerde kedi parazitleri ile ilgili yapılmı~pekçok çali~ma mevcut olup (3,7,12,19,20,21,23) çeşitli faktörlere bağlı olarak değişik paı azit türleri saptanmıştır. Türkiye'de ise konu ilc ilgili çok sınırlı yayın vardır (4,5,6,8,9,14,16).…”
Section: Introductionunclassified